2011
DOI: 10.1002/hbm.21080
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural development: Organizational differences of the fiber architecture between children and adults in dorsal and ventral visual streams

Abstract: Visual perceptual skills are basically mature by the age of 7 years. White matter, however, continues to develop until late adolescence. Here, we examined children (aged 5-7 years) and adults (aged 20-30 years) using diffusion tensor imaging (DTI) fiber tracking to investigate the microstructural maturation of the visual system. We characterized the brain volumes, DTI indices, and architecture of visual fiber tracts passing through white matter structures adjacent to occipital and parietal cortex (dorsal strea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
49
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 56 publications
6
49
0
Order By: Relevance
“…We suggest, however, that early grip selection, as has been proposed for early selection of Reach orientation (McCarty et al 2001), could be mediated by perceptual mechanisms in the ventral visual stream, while dorsal visual control mechanisms, which are needed to accurately synchronize Grasp closure with Reach termination (Goodale and Milner 1992), continue to develop into early childhood. Such a proposition is supported by the fact that older infants in the present study selected not just a power grip, but an exaggerated power grip, compared even with unsighted adults, and also by recent neuroimaging work indicating that connectivity within the dorsal visual stream continues to mature beyond 7 years of age (Loenneker et al 2010). Along this line of thinking, one might also consider that visual control of the Reach might developmentally precede the Grasp because young children favor vision for discriminating object orientation versus haptics for discriminating object size, at least on perceptual tasks (Gori et al 2008).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…We suggest, however, that early grip selection, as has been proposed for early selection of Reach orientation (McCarty et al 2001), could be mediated by perceptual mechanisms in the ventral visual stream, while dorsal visual control mechanisms, which are needed to accurately synchronize Grasp closure with Reach termination (Goodale and Milner 1992), continue to develop into early childhood. Such a proposition is supported by the fact that older infants in the present study selected not just a power grip, but an exaggerated power grip, compared even with unsighted adults, and also by recent neuroimaging work indicating that connectivity within the dorsal visual stream continues to mature beyond 7 years of age (Loenneker et al 2010). Along this line of thinking, one might also consider that visual control of the Reach might developmentally precede the Grasp because young children favor vision for discriminating object orientation versus haptics for discriminating object size, at least on perceptual tasks (Gori et al 2008).…”
Section: Discussionsupporting
confidence: 60%
“…First, haptic feedback may be more reliable than vision due to the ongoing development of postural control (Bertenthal and Hofsten 1998;Hadders-Algra 2013;Thelen and Spencer 1998;Van Der Fits and Hadders-Algra 1998), reaching synergies (Konczak and Dichgans 1997), connectivity within the dorsal visual stream (Loenneker et al 2010), and the ability to re-weight visual and proprioceptive inputs to determine limb location (Bremner et al 2013). Second, haptic dissociation of the Reach and the Grasp may facilitate successful acquisition of the target despite significant kinematic inconsistencies within individual Reach and Grasp components prior to 24 months of age (Konczak and Dichgans 1997;von Hofsten 1991).…”
Section: Discussionmentioning
confidence: 99%
“…As outlined above, our DCM models consisted of bilateral V1, LOC, and right SPC. Reciprocal connections between V1 and (left/right) LOC or right SPC, respectively, as well as a reciprocal link between left and right LOC were taken as core modules for all models tested (Catani, Jones, Donato, & Ffytche, 2003;Felleman & Van Essen, 1991;Lamme & Roelfsema, 2000;Loenneker et al, 2011;Stephan et al, 2007;Zanon, Busan, Monti, Pizzolato, & Battaglini, 2009). Because LOC and SPC have been shown to be related to the processing of illusion strength (Weidner & Fink, 2007), we hypothesized that an interaction of these areas would be mandatory to explain the illusion effect.…”
Section: Dcmmentioning
confidence: 99%
“…Skranes et al (2013) explained reduced surface area of the superior temporal gyrus in VLBW adolescents to be associated with diffuse white matter injury of long association fiber tracks. That region has also connected more to the dorsal stream of adults than in children by fiber connections crossing the splenium of the corpus callosum (Loenneker et al, 2011). All these tracks are at risk for reduced fractional anisotropy in VLBW adolescents (Eikenes, Lohaugen, Brubakk, Skranes, & Haberg, 2011;Skranes et al, 2007), suggesting that subtle white matter injuries in these tracks have indirect effect on cortical maturation.…”
mentioning
confidence: 99%
“…Preterm born children, adolescents and adults have been shown to yield altered networks related to language (Ment, Peterson, Meltzer, et al, 2006; Mullen et al, 2011) (Klaver, Marcar, & Martin, 2011). White matter development of the dorsal visual stream seems to be characterized by strengthened inter-hemispheric connectivity, whereas alteration of regional cortico-cortical connectivity characterizes development of the ventral visual stream (Loenneker et al, 2011). Functional brain imaging studies revealed enhanced dorsal visual stream activity in adults compared to children related to motion defined visual perception as well as visuospatial memory and attention Klingberg, 2006;.…”
mentioning
confidence: 99%